COGNITIVE AND AFFECTIVE RESPONSES OF L1 (AFAN OROMO) IN THE EFL CLASSROOM - Bane, Gemechu; Kitila, Tamene (Universitas Islam Sumatera Utara (UISU), 2023)
One of the most common issues that EFL teachers face in the classroom is the decision of whether or not to use L1 in the L2 classroom. The purpose of this study was to explore the cognitive and affective responses of L1 (Afan Oromo) use in primary school of EFL classrooms. The study employed a qualitative research method with a descriptive case study. Classroom observations and interviews were used to collect data. The Nvivo 12 computer program qualitative data analysis software was used to analyze the collected data. The finding indicated that the most prevalent cognitive reactions were comparing English and Afan Oromo grammatical rules, acquiring new vocabulary, and forming links between Afan Oromo and English. Teachers preferred Afan Oromo for teaching new vocabulary, grammatical lessons, and abstract concepts. Students preferred L1 use for better understanding, mastery of grammar and complicated issues, and a more natural way of expressing themselves because Afan Oromo enables them a more confident sense while expressing their views and keeping the affective filter low. Although using L1 contributes to a better understanding, unguided usage and unsystematized practice of L1 may impede the achievement of desired goals in English teaching and learning.